“Lingkungan Pendidikan Islam dan Problematika: (Kajian Terkait Komponen Utama Lingkungan Pendidikan Islam)” - Mukhlis Mukhlis (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2023)
This research aims to identify the main components associated with the Islamic educational environment in shaping understanding, values, and religious practices in the context of Islam. It also aims to understand various challenges faced in the context of Islamic education. These challenges include a curriculum that is not in line with the current era's development, inadequate teacher qualifications, limited facilities and infrastructure, an excessive traditionalist mindset, and inadequate comprehensive evaluation. The method used in this research is library research based on the search for various articles, journals, and other scholarly works related to pre-defined keywords. The researcher then gathers and selects all the sources to draw conclusions. Analysis of these issues in Islamic education is expected to provide a holistic view for improving the Islamic education system and guiding future efforts to address these challenges. The research findings indicate that the main components of the Islamic educational environment include madrasas or Islamic schools, mosques, religious communities, Islamic books and learning resources, Islamic extracurricular activities, teachers and mentors, Islamic technology and media, Islamic classrooms, and religious education programs. Furthermore, a positive and supportive Islamic educational environment can help students deepen their understanding of Islamic teachings, strengthen their religious identity, and promote tolerance and social values inherited from Islamic teachings. Additionally, some of the challenges in Islamic education include an irrelevant curriculum, low teacher qualifications, limited facilities and infrastructure, traditionalist mindsets, and inadequate comprehensive evaluation. Keywords: Environment, Education, and Challenges